Clinical and genetic analysis VSX1 variants among families with keratoconus in northwest China - Zhang, Jinjin; Cai, Bo; Ma, Limei; Qin, Yixuan; Li, Shuai; Sun, Caihong; Liang, Jing; Han, Yu; Zhuang, Wenjuan (Frontiers in Genetics, 2023)
Purpose: To screen VSX1 gene sequence variations and describe the clinical features of families with keratoconus (KC) from northwest China. Methods: We screened VSX1 sequence variations and clinical data of 37 families including 37 probands with diagnosed KC from Ningxia Eye Hospital (China). VSX1 was screened by targeted next-generation sequencing (NGS) and verified by Sanger sequencing. In silico analysis including Mutation Taster, MutationAssessor, PROVEAN, MetaLR, FATHMM, M-CAP, FATHMM-XF_coding and DANN was performed to identify the pathogenicity of the sequence variations as well as the conserved amino acid variations of VSX1 was implemented by Clustal X. All subjects were assessed in Pentacam Scheimpflug tomography and corneal biomechanical Corvis ST examinations. Results: Five VSX1 gene variants, were identified in six (16.2%) unrelated families with KC. In silico analysis predicted deleterious effects of the three missense variants (p.G342E, p.G160V, and p.L17V) in the encoded protein. Another previously reported synonymous variation (p.R27R) in the first exon and one heterozygous change in the first intron (c.425-73C>T) were identified in three KC families. Clinical examination of the asymptomatic first-degree parents from these six families who shared the gene with the proband had suspected KC changes in topographic and biomechanical markers. These variants co-segregated with the disease phenotype in all affected individuals but not in unaffected family members or healthy controls, though with variable expressivity. Conclusion: The variant p.G342E of VSX1 is implicated in the pathogenesis of KC, which expands the range of the spectrum of VSX1 mutations with an autosomal dominant inheritance pattern and variable expression in the clinical phenotype. Genetic screening combined with clinical phenotype may help in the genetic counseling of patients with KC and identification of individuals with subclinical KC.